UPAYA EFISIENSI DAN PENINGKATAN KETERSEDIAAN NITROGEN DALAM TANAH SERTA SERAPAN NITROGEN PADA TANAMAN PADI SAWAH ( Oryza sativa L.) - Edi Tando (Universitas Tribhuwana Tunggadewi, 2018)
Nutrients or nutrients are important factors for plant growth which can be likened to food substances for plants. One of the factors that support plants to grow and produce optimally is the availability of nutrients in sufficient quantities in the soil. The elements N, P and K, have a very important role in plant growth and production. The purpose of the preparation of the paper is to provide information about efforts to improve efficiency and availability of nitrogen in the soil and nitrogen uptake in lowland rice plants (Oryza sativa L.) Nitrogen has a role as a constituent of enzymes which plays a large role in plant metabolism but is relatively not available to plants. The efficiency of the use of Nitrogen (N) fertilizer in lowland rice can be maximized by way of 1) timely fertilization, 2) planting superior varieties that are responsive to the administration of Nitrogen (N), 3) improving cultivation techniques, 4) regulating the timing of Nitrogen fertilizer (N ) the right during the growing season with Leaf Color Chart (LCC) or Leaf Color Chart (BWD) and 5) NPK fertilization simultaneously. Efforts to increase the availability of nitrogen in the soil and uptake in wetland rice can be done by adding high-quality organic matter, the use of Azotobacter isolates as biological fertilizers to reduce the decrease in soil health due to the input of synthetic chemicals.